Program KKN Edukasi Tajhizul Mayyit bagi Masyarakat Desa Pagur dalam Mewujudkan Generasi Islami Peduli - Junita Ningsih; Nujul Huda; Ermadina Lubis; Annisa Nabila; Siti Aisyah; Riski Maimunah; Ananda Fahmul Afkar; Rosdewi Pulungan; Rohman Rohman (Pemberdayaan Masyarakat : Jurnal Aksi Sosial, 2025)
The implementation of Community Service Program (KKN) in Pagur Village, Panyabungan District, focuses on the Tajhizul Mayyit (Corpse Management) program as a form of community service in the religious field. The main problem faced by the community is the limited knowledge and practical skills in performing fardu kifayah, especially regarding the procedures for managing a corpse according to Islamic sharia. This has the potential to cause difficulties when a death occurs, especially for families who lack a proper understanding of the correct Tajhizul Mayyit procedures. This activity aims to enhance community understanding of fardu kifayah obligations, provide systematic knowledge, and train practical skills in managing corpses, from washing, shrouding, praying, to burying. The methods used in this activity include outreach, deliberation, direct practice, and simulations with the community. Through this method, participants not only understand the theory but are also able to practice it directly. The results of the activity show a significant increase in the understanding and skills of the Pagur Village community. This is evident from the community's enthusiasm in participating in simulations, as well as their ability to perform the Tajhizul Mayyit stages correctly according to procedures. In addition, this activity also fosters a sense of togetherness, social care, and community readiness to help each other in fulfilling fardu kifayah obligations in their environment. Thus, the implementation of the Tajhizul Mayyit program during this KKN activity has made a real contribution to increasing the religious capacity of the community, as well as supporting the realization of a self-reliant, caring, and empowered community in implementing Islamic teachings.